2010
DOI: 10.14442/generalist.33.246
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Discharge Destinations of Cerebrovascular Disease Patients in a Convalescent Rehabilitation Ward: Analysis using ADL Assessment Scale

Abstract: The purposes of this study were to analyze the relationship between the discharge destinations of patients with cerebrovascular diseases (CVD) in our convalescent rehabilitation ward and their levels of activities of daily living (ADL), and also to consider the factors causing those patients difficulties upon discharge. Methods The subjects were 114 CVD patients in our Convalescent Rehabilitation Ward. The investigation was conducted to examine their ADL score, both at hospitalization and at discharge, and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Although there have been only a few studies on the relationship between oral hygiene and function and ADLs, it has been reported that patients discharged home from a rehabilitation ward in the recovery phase have a higher degree of independence in oral cleaning, that tongue movement ability is involved in the acquisition of oral intake at discharge in patients with acute stroke, and that the intervention of a dental hygienist increases the likelihood of discharge [23][24][25]. Furthermore, our previous study showed that tube-fed patients with poor oral hygiene on admission had poor reacquisition of oral intake [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there have been only a few studies on the relationship between oral hygiene and function and ADLs, it has been reported that patients discharged home from a rehabilitation ward in the recovery phase have a higher degree of independence in oral cleaning, that tongue movement ability is involved in the acquisition of oral intake at discharge in patients with acute stroke, and that the intervention of a dental hygienist increases the likelihood of discharge [23][24][25]. Furthermore, our previous study showed that tube-fed patients with poor oral hygiene on admission had poor reacquisition of oral intake [26].…”
Section: Discussionmentioning
confidence: 99%
“…The role of a dental hygienist in a Kaifukuki rehabilitation ward is to coordinate with the dentist, evaluate oral hygiene, create programs for oral hygiene procedures, and provide guidance to patients and their families regarding oral care materials, such as toothbrushes [28]. It has been reported that the interventions of dental hygienists in Japanese rehabilitation wards are associated with an increase in FIM scores at discharge and the proportion of patients returning home and a reduction in hospital stay and mortality [10,24]. This suggests that the role of dentists and dental hygienists in Kaifukuki rehabilitation wards is substantial.…”
Section: Discussionmentioning
confidence: 99%
“…Sakamoto & Yamamoto (2019) suggest that higher levels of impairment in daily living are strongly reflected in the severity criteria indicated by the B score. Ohmori et al (2010) argued that in patients with cerebrovascular disease admitted to a recovery rehabilitation ward, the B score indicates daily functioning that makes discharge home difficult. Therefore, the B score is an indicator of the level of activities of daily living and it is an important independent variable for predicting the performance index score.…”
Section: B Score On Admission and Cutoff Valuesmentioning
confidence: 99%
“…Most of these studies have focused on stroke patients, and have revealed that motor FIM score on admission, cognitive FIM score on admission, nutritional status, dysphagia, age, hemispatial neglect, and socioeconomic status are important independent variables as predictors of the FIM score on discharge and recovery of physical function (Bagg, Pombo, & Hopman, 2002;Kokura, Maeda, Wakabayashi, Nishioka, & Higashi, 2016;Yoshimura, Wakabayashi, Bise, Nagano, Shimazu, Shiraishi, Yamaga, & Koga, 2019;García-Rudolph, Cegarra, Opisso, Tormos, Bernabeu, & Saurí, 2020;Hiragami, Hiragami, & Inoue, 2019). In addition to this, some studies have found that the aforementioned B score items "transfer," "communication of will to others," "transfer method," and "oral cleanliness" are important items that affect discharge home (Ohmori et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation